Religie Indii w relacjach arcybiskupa Władysława Michała Zaleskiego opublikowanych w „Misjach Katolickich" (1891-1897) - BOGUSIAK, MAŁGORZATA (Annales Missiologici Posnanienses, 2010)
Archbishop Władysław Zaleski was one of the best known Polish missionaries in history of Catholic Church. He spent over 30 years in India, where he founded first theological seminary in Ceylon and established indigenous hierarchy in Indian Church. During his mission he used to write a lot of letters, which were published in periodical “Missye Katolickie”. This text presents archbishop’s attitude toward religions he met in India - Buddhism and Hinduism. As many missionaries in his times he believed that only Christianity is true religion and other people outside Catholic Church were pagans. In his opinion those Indian indigenous religions were worshiping devil. Text shows also Zaleski’s opinion about Budda and nirvana.